Proceedings from the Nordcode Seminar - Participation and Dialogue - Nielsen, Liv Merete; Vihma, Susann; Gulden, Tore; Berg, Arild (FormAkademisk, 2012)
This issue of FORMakademisk is the result of a cooperative effort involving the Nordcode research network, the Department of Product Design at Akershus University College and the FORMakademisk. It builds on the Participation and Dialogue seminar, held in May 2010, which was supported by Nordforsk, The Norwegian Research Council and Kjeller Science Park.